Herbal Medicine in Treatment of Recurrent Aphthous Stomatitis: A Literature Review - Raziehsadat Rezvaninejad; Nader Nabavi; Seyed Mohammadreza Khoshroo; Narjes Torabi; Zahra Atai (Islamic Dental Association of Iran, 2017)
Background and Aim: Recurrent aphthous stomatitis (RAS) is the most common oral mucosal lesion in the general population. Different treatments have been used for RAS, including herbal medicine. In this study, the randomized clinical trials (RCTs) on the effect of medicinal plants on RAS were systematically searched and reviewed. Materials and Methods: The literature from 1985 to 2015 in the PubMed, Scopus, Embase, Cochrane and Medline databases were searched using the relevant keywords. After screening, 15 articles were reviewed. Results: Herbal medicine has been used in the treatment of RAS for reducing the pain and healing time and promoting ulcer healing. Most herbal products are in the form of mouthwash. Conclusion: Herbal medicine can be used as an alternative therapy for RAS.